2008
DOI: 10.1037/0893-164x.22.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Fitting in and feeling fine: Conformity and coping motives as mediators of the relationship between social anxiety and problematic drinking.

Abstract: The present research was conducted to clarify the relationships among social anxiety, alcohol consumption, alcohol-related problems, and negative-reinforcement drinking motives among college students. Heavy drinking students (N = 316, 53.80% female) completed self-report measures of social anxiety, alcohol consumption, alcohol-related problems, and drinking motives. Findings indicated that students higher in social anxiety consumed less alcohol but experienced more negative consequences. Moreover, the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
117
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 69 publications
13
117
0
1
Order By: Relevance
“…In a review of 82 studies examining drinking motives (social, enhancement, and coping) among adolescents and young adults, Kuntsche et al (2005) found that poor mental health (e.g., high levels of anxiety sensitivity, depression, and negative self-views) was associated with coping motives toward drinking. Among students with anxiety symptomatology, both coping and conformity motives appear to be most strongly endorsed (Lewis et al, 2008;.…”
Section: Mental Health and Drinking Motives On Alcohol Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…In a review of 82 studies examining drinking motives (social, enhancement, and coping) among adolescents and young adults, Kuntsche et al (2005) found that poor mental health (e.g., high levels of anxiety sensitivity, depression, and negative self-views) was associated with coping motives toward drinking. Among students with anxiety symptomatology, both coping and conformity motives appear to be most strongly endorsed (Lewis et al, 2008;.…”
Section: Mental Health and Drinking Motives On Alcohol Outcomesmentioning
confidence: 99%
“…Enhancement motives (e.g., for fun or excitement) are found to predict alcohol-related consequences, but only indirectly through heavy levels of drinking (Cooper et al, 1992;Merrill and Read, 2010; for review, see Kuntsche et al, 2006). The negative reinforcing motives of coping and conformity drinking remain strong predictors of alcohol-related consequences, over and above drinking levels (Cooper, 1994;Kassel et al, 2000;Lewis et al, 2008). Given the important role of different types of drinking motives in the connection between mental health and drinking outcomes, it is important to examine drinking motivations as mediators of this relationship.…”
Section: Mental Health and Drinking Motives On Alcohol Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although norms may be especially relevant for socially focused drinkers because of the social comparison component of norms, they may be less relevant for coping-motivated drinkers. Drinking to cope with negative affect has been identified as an indicator of heavy (Cooper et al, 2000;Labouvie & Bates, 2002;Montgomery et al, 1993) and problematic drinking (Kuntsche et al, 2005(Kuntsche et al, , 2008Lewis et al, 2008;Martens et al, 2008).…”
Section: P Ersonalized Normative Feedback (Pnf)mentioning
confidence: 99%
“…[11][12][13][14] A couple of longitudinal studies have also shown that drinking motives predict changes in alcohol use over time, e.g., higher enhancement motives predict an increase in RSOD 15,16 and higher enhancement or coping motives predict an increase in alcohol-related problems. [17][18][19] The theoretical model of drinking motives assumes that they also depend on reinforcement achieved through feedback loops from past drinking, 8,9,20 i.e., the experience of positive effects of drinking in a group is likely to encourage further drinking for social motives.…”
Section: Introductionmentioning
confidence: 99%